Sistem Pakar untuk Mendiagnosa Penyakit Telinga Hidung dan Tenggorokan (THT) menggunakan Metode Forward Chaining - Iwan Giri Waluyo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The latest developments in the medical world use computers to help diagnose and prevent and treat a disease. In the concept of tracking in finding solutions with an artificial intelligence approach, there are various methods that can be applied to overcome the problem of uncertainty when the tracking process occurs. One of them is the Forward Chaining method. This study aims to develop an expert system that is used for the diagnosis of Ear, Nose and Throat diseases, where users can self-diagnose based on the symptoms they feel. For that we need a method to overcome these problems. In this study a method for self-diagnosing based on the symptoms he felt in tracking cases was applied to diagnose ENT (Ear, Nose and Throat) diseases. The subject of this study is the tracking process to determine ENT disease with the forward chaining model of reasoning. The research method begins with data analysis, system design, coding using Java programming, system testing with white box and black box tests. From the research conducted to produce a software that is capable of determining disease in ENT by applying the forward chaining method. The system trial results show that this application is feasible and can be used.